Vocabulary learning strategies of year 6 pupils in a primary school in Kuala Terengganu / Zulbitah Sidek - Sidek, Zulbitah (2013)
The present research is to study vocabulary learning strategies (VLS) of Year 6 pupils in a school in Kuala Terengganu, Terengganu in comprehending reading materials and the factors that influenced their choices. The research objectives are to determine vocabulary strategies of Year 6 pupil, their preferable vocabulary learning strategies in comprehending a text and to examine factors that influence pupils' choice of vocabulary learning strategies. The vocabulary learning strategies that were looked at in the research were task-dependent guessing, dictionary use, note-taking and memory strategies. Since vocabulary is an important knowledge in the process of learning a language, language learners need to acquire vocabulary knowledge because it is one of the linguistic subskills in language. Without sufficient vocabulary knowledge, a language learner will have difficulties in understanding a text or any printed material. A convenient sampling of 35 Year 6 pupils in a primary school in Kuala Terengganu, Terengganu were chosen as the respondents of the study. They were 22 female and 13 male respondents. All the respondents were 12years old at the time of the study. In this research mixed approach is used; quantitative and qualitative. This was accomplished by administering a questionnaire (quantitative) and an interview (qualitative) to the respondents. The first findings on the belief of the respondents towards VLS revealed that they believed all the strategies listed would help them in attaining and getting the meaning of words in dealing with reading comprehension. All the strategies listed in the questionnaires are being applied by the respondents in this study mostly the dictionary strategies. A few respondents used note-taking and guessing strategies. However, the least used strategy was memory strategies. The factors that influenced the pupils' choice of VLS were the motivation that they got from their teacher, parents and the culture of Asian pupils of not asking help from their friends. They also preferred the fastest and easiest way to get meaning. The implication of the study is that English teachers in the school should be sensitive and aware of the vocabulary learning strategies preferred by their pupils and guide them to use the strategies efficiently and effectively. It is recommended that sample from different proficiency levels, young learners from other ages, increasing the size of the sample and investigates using different VLS taxonomy proposed by other researchers for future research.